Sambal Roa Innovation: A Traditional Culinary Business Opportunity in Sidoarjo, Indonesia - Anatasya Angelina; Siti Aisyah; Umi Nur Hastuti (EduInovasi: Journal of Basic Educational Studies, 2025)
This study explores the potential of sambal roa as an innovative culinary product in Sidoarjo, Indonesia. Sambal roa, made from smoked roa fish and local spices, offers a unique flavor that aligns with the rising consumer interest in practical and authentic spicy condiments. Using a qualitative method involving observations and surveys in local markets, the study analyzes consumer awareness, taste preferences, and purchase intentions. Findings reveal a strong interest in sambal roa among Sidoarjo consumers, particularly those aged 20–50, due to its practicality, distinctive aroma, and spicy savory flavor. The study concludes that sambal roa has strong potential to compete in both local and broader markets, especially with proper branding and digital marketing strategies.